Modeling spontaneous shear bands evolution in thick-walled cylinders subjected to external High-strain-rate loading. (15th October 2016) - Liu, Mingtao; Guo, Zhaoliang; Fan, Cheng; Tang, Tiegang; Wang, Xiaoyan; Hu, Haibo
Highlights: A probability factor was introduced to describe the non-uniformity of yield stress. A modified J-C model was proposed according to the DRX in shear bands. The evolution of spontaneous shear bands was numerically studied. The mechanisms of bifurcation, intersection and countercheck were analyzed. The single direction spiral pattern of shear bands in TWC was replicated. Abstract: The evolution of spontaneous shear bands in a 304 L stainless steel (304LSS) cylinder subjected to external explosive loading was numerically studied. As an instability process, the initiation of a shear band is strongly dependent on the non-uniformities of the material. A probability factor satisfied the Gaussian distribution was introduced into the macroscopic constitutive relationship to describe the nonuniform distribution of the local yield stress in material. On the basis of that the material inside the shear band undergoes a dynamic recrystallization process (DRX), the traditional J-C model was modified. The item melting temperature, Tm, was replaced by the temperature for DRX, TDRX . Specifically, the TDRX was set to be 0.4 Tm at high strain rates (>10 3 s −1 ) for 304LSS. Using the probability factor and the modified J-C model, we successfully simulated the initiation and propagation of spontaneous shear bands in the collapsing 304LSS cylinder. The pattern of the shear bands agrees well with the experimental observations, at both early stage and late stage. The perturbation amplitude was found to have a slight influence on the shear band spacing and the initiating time of shear bands. Some morphological characteristics of shear bands (such as bifurcation, intersection and countercheck), which are familiar in experiments, were also observed in our simulation. The formation mechanisms of these phenomena were analyzed on the basis of their evolvements. The shear bands in TWC show a single direction spiral pattern, in other words, almost all the shear bands simultaneously propagate along a given direction, clockwise or counterclockwise. The single direction spiral pattern is closely related to the work-hardened layer in the internal surface of the 304LSS cylinder. The microstructures in the work-hardened layer (about 30  µ m) are significantly different from those in the base material. The grains have been rotated and elongated along the cutting direction during the machining. In the simulation, periodic single direction spiral perturbations were applied to describe the grain orientation in the work-hardened layer, and the single direction spiral pattern of shear bands in 304LSS TWC was successfully replicated. While the spacing of the single direction spiral perturbations exceeds a certain value, the shear bands switch back to the bidirectional spiral pattern. The critical spacing for the pattern transition was found to be close to the spacing of well-developed shear bands. Graphical abstract: